Review of the fractionation of medicines available in solid formulations (tablets) - Baudrit Carrillo, Olga (2016)
Not always people receive the just dose of active ingredient required for his health problem. To obtain success in pharmacology treatment, sometimes the physicians prescribe drugs in a dose that is impossible obtain in the market because this specific strength does not exist in the pharmaceutical form that they proposed. This is the case of some tablets, which need to be divided to achieve this objective. Several reasons are to justify the need to split pills, since there exist some consequences of this act in different contexts. Laboratories produce pharmaceutical forms with Good Manufacturing Practices, but not all medications are designed to be split. Dividing a scored tablet into two parts, it is no guarantee to find accurately the half dose in each fraction. More research is required in Costa Rica, Central America to know the magnitude of the actual situation in this topic.